Pelatihan Penggunaan AI Magic School sebagai Upaya Penguatan Literasi Digital Guru dalam Mendukung Transformasi Pendidikan di Era Globalisasi - Hardi Alunaza; Aliyah Nur'aini Hanum; Dea Varanida; Mentari Mentari; Ratu Zahirah Lutfie; Muhammad Fadhlan (Abdimas Mandalika, 2026)
Abstract:  The integration of technology in education is part of a soft power strategy to enhance global competitiveness, and AI plays a role in transforming learning communication patterns to become more interactive and tailored to students’ needs. However, the implementation of AI in Indonesia still faces several challenges, particularly the low level of teachers’ digital literacy, which may widen the digital divide. This community service activity aims to improve the understanding and skills of teachers in Singkawang City in utilizing the AI Magic School platform to support the learning process. The implementation method was carried out in a participatory manner through four stages: preparation and observation, training, evaluation, and reporting. The activity was conducted from May to August 2024. The results show a significant improvement in digital literacy, understanding of AI usage, and teachers’ confidence in integrating technology into the learning process. The use of AI Magic School also encourages a shift in communication patterns from teacher-centered to student-centered learning and improves teachers’ work efficiency through various features such as lesson planning, material development, and evaluation tools. Thus, the training on the use of AI Magic School has proven to be effective in supporting educational transformation, enhancing the quality of learning communication, and strengthening the competitiveness of human resources in the era of globalization.Abstrak: Integrasi teknologi dalam pendidikan merupakan bagian dari strategi soft power untuk meningkatkan daya saing global dan AI berperan dalam mengubah pola komunikasi pembelajaran menjadi lebih interaktif dan berbasis kebutuhan peserta didik. Namun, implementasi AI di Indonesia masih menghadapi kendala, terutama rendahnya literasi digital guru yang berpotensi memperlebar kesenjangan digital. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan keterampilan guru di Kota Singkawang dalam menggunakan platform AI Magic School sebagai pendukung pembelajaran. Metode pelaksanaan dilakukan secara partisipatif melalui empat tahapan, yaitu persiapan dan observasi, pelatihan, evaluasi, serta pelaporan. Kegiatan dilaksanakan selama Mei–Agustus 2024. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam literasi digital, pemahaman penggunaan AI, serta kepercayaan diri guru dalam mengintegrasikan teknologi ke dalam pembelajaran. Pemanfaatan AI Magic School juga mendorong perubahan pola komunikasi dari teacher-centered menjadi student-centered, serta meningkatkan efisiensi kerja guru melalui berbagai fitur seperti perencanaan pembelajaran, pembuatan materi, dan evaluasi. Dengan demikian, pelatihan penggunaan AI Magic School terbukti efektif sebagai upaya mendukung transformasi pendidikan, meningkatkan kualitas komunikasi pembelajaran, serta memperkuat daya saing sumber daya manusia di era globalisasi.